TEACHING OF STOCHASTIC ELEMENTS IN SCHOOLS OF UZBEKISTAN AND SOME FOREIGN COUNTRIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes the teaching of stochastic elements in schools in foreign countries and Uzbekistan.